2015
DOI: 10.1371/journal.pone.0122311
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Association between Facial Disgust Recognition and Estradiol Levels in Naturally Cycling Women

Abstract: Subtle changes in social cognition are associated with naturalistic fluctuations in estrogens and progesterone over the course of the menstrual cycle. Using a dynamic emotion recognition task we aimed to provide a comprehensive description of the association between ovarian hormone levels and emotion recognition performance using a variety of performance metrics. Naturally cycling, psychiatrically healthy women attended a single experimental session during a follicular (days 7–13; n = 16), early luteal (days 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…In the natural menstrual cycle, increased levels of estrogen/estradiol typical of the follicular phase favored the recognition of facial expressions of emotion. This finding lends support to the view that ovarian hormones trigger evolutionary adaptations that are relevant for emotional competence, with the possible purpose of increasing mating chances (Derntl et al, 2008a ; Kamboj et al, 2015 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the natural menstrual cycle, increased levels of estrogen/estradiol typical of the follicular phase favored the recognition of facial expressions of emotion. This finding lends support to the view that ovarian hormones trigger evolutionary adaptations that are relevant for emotional competence, with the possible purpose of increasing mating chances (Derntl et al, 2008a ; Kamboj et al, 2015 ).…”
Section: Discussionsupporting
confidence: 77%
“…However, specific analyses about the association between hormone levels (independently of menstrual cycle phase) and accuracy of emotional judgment showed that higher estrogen/estradiol levels were linked to improved recognition of fear (Pearson and Lewis, 2005 ) and decreased accuracy in the recognition of anger (Guapo et al, 2009 ; Kamboj et al, 2015 ) and disgust (Kamboj et al, 2015 ). In respect to progesterone, the associations found were less evident, but increased progesterone levels have been associated with global impairment in FEP consisting of increased response time, increased response biases, negative biases, and decreased accuracy of emotional judgment (Conway et al, 2007 ; Derntl et al, 2008a ; Kamboj et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that use of hormone-based contraceptive pill is common in the United States and many European countries, with approximately a quarter of women using them (Enewold et al, 2010). The alternative approach of testing non-contraceptive using, regularly cycling women at a specific phase in their menstrual cycle (Kamboj, Krol, & Curran, 2015;Soni, Curran, & Kamboj, 2013) is cumbersome, and does not improve generalisability. Furthermore, studies limited to men are also problematic, especially given that there is a >2-fold higher lifetime prevalence of PTSD among women (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen levels appear to influence the perception of some facial displays of emotion (Guapo et al, 2009;Kamboj, Krol, & Curran, 2015). Estrogen levels impact mood (for a review Newhouse & Albert, 2015).…”
Section: Introductionmentioning
confidence: 99%